Theoretical studies and calculations of wastewater treatment in trickling biofilters - Kolpakova, Olga (KNUCA, 2015)
On the basis of the analysis of existing models and methods of calculation, proposed a general mathematical model of the process of removal of organic contaminants in an aerobic biological wastewater treatment in trickling biofilters with sufficient support biooxidation by oxygen. Results of comparison of theoretical calculations with experimental data obtained by different authors in trickling biofilters with different loading are presented. As the results, the theoretical calculations are in general well correlated with the experimental data.
ТЕОРЕТИЧЕСКИЕ ИССЛЕДОВАНИЯ И РАСЧЕТЫ ОЧИСТКИ СТОЧНЫХ ВОД НА КАПЕЛЬНЫХ БИОФИЛЬТРАХ
Keywords: biofilter; waste water; biological film; model; treatment; сточные воды; биофильтр; биологическая пленка; модель; очистка; 628.3